1976
DOI: 10.1056/nejm197609022951003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Closure of Patent Ductus Arteriosus in the Premature Infant

Abstract: The prostaglandins affect smooth-muscle tone of the ductus arteriosus. Patent ductus often complicates the clinical course of prematurely born infants with respiratory-distress syndrome. In the present study, a single oral or rectal dose of a potent inhibitor of prostaglandin synthesis, indomethacin, was administered to six consecutive premature infants with the syndrome who would otherwise have undergone surgical ligation of the patent ductus. Within 24 hours all the clinical symptoms and physical, echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
7

Year Published

1977
1977
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(124 citation statements)
references
References 23 publications
6
111
0
7
Order By: Relevance
“…More than three decades after the first reports of medical treatment of the PDA, 47,48 management remains heterogeneous and controversial and ideal timing and criteria for various treatments remain still to be established. [49][50][51][52] Some authors have concluded that there is a need for new controlled, randomized trials to reexamine the benefits and risks of different approaches to PDA treatment 35,37 and others considered that clinical trials are needed to determine whether any interventions intended to close the PDA reduce mortality and morbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…More than three decades after the first reports of medical treatment of the PDA, 47,48 management remains heterogeneous and controversial and ideal timing and criteria for various treatments remain still to be established. [49][50][51][52] Some authors have concluded that there is a need for new controlled, randomized trials to reexamine the benefits and risks of different approaches to PDA treatment 35,37 and others considered that clinical trials are needed to determine whether any interventions intended to close the PDA reduce mortality and morbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled and uncontrolled clinical trials showed that surgical ligation 24,25 and indomethacin 26,27 effectively achieve ductal closure. Describing a widespread impression, Kitterman commented.…”
mentioning
confidence: 99%
“…This infant was delivered by Caesarean section at 30 weeks because of severe toxemia and acute fetal distress. After intensive treatment which included administration of Indomethacin in order to close the patent ductus arteriosus (according to FRIEDMAN et al [5]), the infant made an uneventful recovery. It is quite difficult to explain the incidental RDS in case No.…”
Section: Discussionmentioning
confidence: 99%